Oragentburg: A Platform Supporting Organisation-Based Programming - Yin Chan; Xinjun Mao; Cuiyun Hu; Huiping Zhou; Jianmin Zhao (2012 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2012)
Organisation-based programming promises that it can facilitate the development and management of dynamic and flexible software systems with high-level organisational abstractions. However, the adoption of such approach in industry has been sluggish, largely due to the lack of efficient programming languages and their supporting platforms. Oragentburg is a platform which can support the running of dynamic, open, and flexible multi-agent systems developed in Or agent: a programming language which provides explicit organizational primitives and programming mechanisms for constructing multi-agent systems in an organisation-based manner. This platform meet the requirements proposed by Or agent language by providing a series of services such as managing lifecycle of agents and agent groups, supporting the dynamic adjustment of agent behaviour with role enactment mechanism, supporting role-based message transports among agents, etc. This paper introduces the general architecture of Oragentburg platform and its implementation.